Produksi Etanol Proses Sinambung dengan Schizosaccharomyces Pombe - Febriningrum, Panca Nugrahini (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2009)
Ethanol is one of fermentation products which are mostly used as solvent in pharmaceutical and chemical industries. Ethanol production by fermentation generally uses yeast from Saccharomyces and Schizosaccharomyces. The fermentation of ethanol by both processes yields great quantities of ethanol. Optimum productivity in ethanol fermentation by continuous process using Schizosaccharomyces pombe was obtained at initial substrate concentration of 200g/L, with value as much of 7.342g/Lhour at dilution rate of 0.1/hour, 4.643 g/Lhour at dilution rate of 0,06/hour and 3.213g/Lhour at dilution rate of 0.04/hour. The highest value of ethanol coefficient YP/S obtained at initial substrate concentration of 100g/L was as much of 0.461 at batch process, while values of ethanol coefficient YP/S obtained were in the range of 0,477-0,511 in continuous process, which were higher than those of batch process.Keywords: continuous process, ethanol, schizosaccharomyces pombe